Comparison of complications between transcatheter and surgical ventricle septal defect closure: a single-center cohort study (Medical Journal of Indonesia, 2020)
BACKGROUND Some ventricular septal defects (VSDs) require an interventional procedure for closure. Transcatheter and surgical closures of VSD have similar effectiveness, but transcatheter VSD closure is considered associated with less complication than surgical closure. This study aimed to compare mid-term or long-term complications of transcatheter and surgical VSD closures. METHODS This was a retrospective cohort study compared the complication rates of transcatheter and surgical VSD closures performed in Cipto Mangunkusumo Hospital from January 1, 2010, to April 30, 2017, with 34 subjects in each group. The inclusion criteria were as follows: single lesion outlet perimembranous or doubly committed subarterial VSD, age 218 years, body weight >8 kg, and no arrhythmia. Electrocardiography and echocardiography were done to collect primary data. Other data were collected from medical records. Mid-term complications occurred 124 months after interventional closure. Long-term complications occurred 24 months after interventional closure. Complications were arrhythmia, valve regurgitation, and residual shunt. Data were analyzed by chi-square test. RESULTS The rate of worsening valve regurgitation was higher in the transcatheter group than in the surgical group (16 versus 11, p = 0.322). The number of patients with residual shunts were similar between the transcatheter group and surgical group (5 versus 5; p = 1.000). Both complications were found in mid- and long-term. Arrhythmia as a long-term complication occurred in five and seven patients in the transcatheter and surgical groups, respectively (p = 0.752). CONCLUSIONS Transcatheter and surgical VSD closures have similar mid or long-term complications.